Developing Ecotourism in Cambodia : Cambodia Policy Note - Rawlins, Maurice Andres (Washington, DC: World Bank, 2022)
Cambodia is blessed with a vast array of spectacular landscapes and pristine natural riches. This natural beauty, along with the country’s cultural wonders, is what ecotourists come to Cambodia for. The opportunities for supporting the expansion of the ecotourism industry to meet this demand are immense. Ecotourism involves traveling to areas of pristine nature, usually protected, to appreciate the environment while causing minimal impact. Ecotourism offers multiple benefits. However, the impact of Coronavirus (COVID-19) on the tourism industry in Cambodia has been significant. The epidemic has escalated rapidly from a health emergency to a full economic crisis. Since the beginning of the outbreak, several local and international surveys have been conducted that can help us understand the impacts of Coronavirus (COVID-19) on Cambodia’s tourism sector and guide the recovery. This note presents policy options to support the sustainable development of ecotourism as part of a broader strategy for sustainable management of the country’s natural capital. In addition, the policy note provides recommendations to the Royal Government of Cambodia (RGC) to help the recovery of the tourism sector post-COVID-19.